Utilization of agricultural wastes as fillers in thermoplastics composites - Hassan, Azman; Rahmat, Abdul Razak; Abu Bakar, Aznizam; Ahmad, Mazatusziha (Kolej Universiti Sains dan Teknologi Malaysia (KUSTEM), 2004)
The concept of cost reduction in plastics by use of fillers has been known throughout the ages. By the appropriate selection and optimization of such materials, not only the economic but other properties such as processing and mechanical behaviour can be improved. The growing interest in environmentally friendly materials has greatly increased the interest in the use of natural fillers derived from agricultural sources in plastics composites. These natural fillers have the advantages of low densities, very low cost, non-abrasiveness, higher filling levels, recyclability, biodegradability and renewable nature. As the field of plastics develops and expands, a variety of naturally occurring materials are explored such as wood flour, empty fruit bunch (EFB) and rice husk (RH). This paper reports the recent development and current work on the utilization of EFB ad RH as fillers in thermoplastics composites. The study has shown that the incorporation of RH and EFB fillers has resulted in the increase of flexural modulus indicating a improvement in stiffness. The flexural modulus increase further with increasing both of RH and EFB loadings. However, impact strength of both EFB and RH filled PVC-U composites.